Reach fo the Top : Women and the Changing Facts of Work Life / Nancy A. Nichols, Rosabeth Moss Kanter - Nichols, Nancy A.
Reach for the Top examines the challeges, frustrations, and opportunities facing today's professional women: gender stereotypes and the conflicts they create, the glass ceiling, sexual harassment, discrimination, and work/family pressures. Featuring Harvard Business Review case studies, essays by leading analysts (including Judith Rosener and Felice Schwartz, whose article started a national debate over the "Mommy Track"), and inspiring stories from successful women managers, these 12 HBR articles provide a fresh look at the issues women face at work